Tourism - Abdul Rehman Khan, Syed (IntechOpen, 2021)
Tourism was booming until 2019 when the COVID-19 pandemic hit. Since then, tourism and related industries have suffered from negative economic impacts. This book examines current challenges and opportunities in the tourism industry using case studies from different parts of the world. It also examines the challenges and obstacles faced by the tourism sector due to lack of environmental policies, high crime rates, and poverty.